2020
DOI: 10.1093/ofid/ofaa250
|View full text |Cite
|
Sign up to set email alerts
|

Serum Iron Level as a Potential Predictor of Coronavirus Disease 2019 Severity and Mortality: A Retrospective Study

Abstract: Abstract Background Various types of pulmonary diseases are associated with iron deficiency. However, information on iron status in coronavirus disease 2019 (COVID-19) is scarce. Methods This study included 50 hospitalized patients with confirmed COVID-19. The rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
137
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(162 citation statements)
references
References 17 publications
21
137
0
4
Order By: Relevance
“…Serum iron level was reported as a potential predictor of COVID-19 severity and mortality [29]. Decreased serum iron level could predict the transition of COVID-19 from mild to severe and critical illness [30,29], which was in agreement with our ndings. Zinc is one of the micronutrients that could be consumed to reduce the intensity of SARS-CoV-2 infection and perhaps lessen the respiratory tract infection through the antiviral actions [7].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Serum iron level was reported as a potential predictor of COVID-19 severity and mortality [29]. Decreased serum iron level could predict the transition of COVID-19 from mild to severe and critical illness [30,29], which was in agreement with our ndings. Zinc is one of the micronutrients that could be consumed to reduce the intensity of SARS-CoV-2 infection and perhaps lessen the respiratory tract infection through the antiviral actions [7].…”
Section: Discussionsupporting
confidence: 91%
“…For iron, systemic dysregulation resulted from COVID-19 hyperin ammation has been recently reviewed [28]. Serum iron level was reported as a potential predictor of COVID-19 severity and mortality [29]. Decreased serum iron level could predict the transition of COVID-19 from mild to severe and critical illness [30,29], which was in agreement with our ndings.…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, optimal iron status may be crucial for better disease prognosis. So, a retrospective study based on 50 hospitalized Chinese subjects with confirmed COVID-19, demonstrated that 90% of these subjects (45) showed abnormally low serum iron concentrations (<7.8 μM) and the severity of the disease negatively correlated with serum iron concentrations [ 124 ]. For this reason, populations with lower iron status could be more prone to suffer a mild to severe (or critical) symptomatology of COVID-19 and the fact of monitoring patient iron levels has been proposed as a potential early marker to predict COVID-19 severity and mortality [ 124 ].…”
Section: Association Between 10 Critical Micronutrients and Prevalmentioning
confidence: 99%
“…Iron metabolism disturbance has been widely reported in various infectious diseases. S. Typhi competes with humans for iron utilization by increasing the expression of hepcidin, which can restrict iron uptake and macrophage iron release, and the high serum hepcidin leads to hypoferremia [8]; COVID-19 infection resulted in hyperferritinemia due to cytokine storms, and serum iron transferrin saturation in intensive care unit (ICU) patients infected with COVID-19 was extremely reduced for the rst 2 days and then increased from days 3 to 6 [9,27,28]. In this study, we found that serum iron was signi cantly decreased in S. Enteritidis patients, and it seemed to be lower in patients with more serious symptoms; with the recovery of patients' symptoms, serum iron increased.…”
Section: Discussionmentioning
confidence: 99%